FORMULASI KEBIJAKAN SISTEM TRANSPORTASI LAUT - Kadarisman, Muh; Yuliantini, Yuliantini; Majid, Suharto Abdul (JURNAL MANAJEMEN TRANSPORTASI & LOGISTIK, 2016)
The aims of this research is to analyze the policy of sea transport in the realization of modern sea toll transportation and development. The research uses descriptive-qualitative. The result shows: 1) government’s policy regarding sea toll is to ship transport, guarantee the availability of goods, reduce disparity cost and ensure continuity service transport of goods to regional, remote, outermost and border; 2) sea transport development policy is to enhance the role of national shipping leet both domestic and export-import transportation by imposing cabotage principle; abolish unoficial charges in ports through improved coordination of all relevant institutions and the process of loading and unloading goods that meet international shipping standards and the implementation of the International Ship and Port Security; restructure shipping legislation and its implementation, as well as institutional sub-sector of sea transport in order to create conditions that will attract private investment in the construction of sea transportation infrastructure; 3) sea transportation policy is set to increase nasional development to transport people, goods and information. This policy functions as supporting system to achieve the optimum allocation of economic resources in order to provide equitable, and affordable purchasing power services.